Histocompatibility antigens and post-encephalitic Parkinsonism. - Lees, A J (1982)
Twenty-one patients with Parkinsonism secondary to von Economo's encephalitis were typed for HLA-A, B, C and DR antigens. No differences were found in the phenotype frequencies of these antigens compared with controls. This finding fails to support the hypothesis of genetic susceptibility to post-encephalitic Parkinsonism.